Market uncertainty and risk transfer in REDD projects. (4th July 2017) - Chesney, Marc; Gheyssens, Jonathan; Troja, Bruno
ABSTRACT: The central role played by deforestation in the increase in global CO2 emissions has recently justified the development of new schemes which offer compensation in exchange for reductions in emissions from deforestation (Reducing Emissions from Deforestation and Forest Degradation, REDD). The design of REDD projects can be based on market prices to set how deforesters are compensated for avoiding deforestation. With limited experiments involving a true market integration of REDD, it remains, however, difficult to assess that the potential impact market price uncertainties may have on the targets of the protective scheme. The goal of this article is to assess the optimal choices of a forest owner, in terms of his combined decision of choosing when to protect his forest, and the deforestation rate prior to it, given his option to enter an irreversible REDD scheme that provides him with uncertain cash flows under different risk aversion scenarios.